2005
DOI: 10.1007/s00419-005-0443-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiplane study on confocally elliptical inhomogeneity problem using an alternating technique

Abstract: This paper presents a novel efficient procedure to analyze the two-phase confocally elliptical inclusion embedded in an unbounded matrix under antiplane loadings. The antiplane loadings considered in this paper include a point force and a screw dislocation or a far-field antiplane shear. The analytical continuation method together with an alternating technique is used to derive the general forms of the elastic fields in terms of the corresponding problem subjected to the same loadings in a homogeneous body. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Xiao and Chen [11] investigated the interaction between an edge and a coated circular inclusion with the Muskhelishvili complex method. Shen et al [12] solved the antiplane problem for a screw dislocation in a three-phase elliptical medium by using the conformal mapping and alternating technique. Chao et al [13] employed the analytical continuation method and alternating technique to solve the plane elasticity problem for an arbitrary point singularity in a three-phase composite cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao and Chen [11] investigated the interaction between an edge and a coated circular inclusion with the Muskhelishvili complex method. Shen et al [12] solved the antiplane problem for a screw dislocation in a three-phase elliptical medium by using the conformal mapping and alternating technique. Chao et al [13] employed the analytical continuation method and alternating technique to solve the plane elasticity problem for an arbitrary point singularity in a three-phase composite cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the stresses within a multiphase elliptical inclusion are uniform provided that all interfaces consist of confocal ellipses. A novel efficient procedure to analyze the two-phase confocally elliptical inclusion embedded in an unbounded matrix under antiplane loadings was provided [8].Within the framework of linear piezoelectricity, an effective method was developed and used to derive an analytical solution for the problem of a confocally multicoated elliptical inclusion embedded in an unbounded matrix which is subjected to arbitrary electromechanical loadings [9].…”
Section: Introductionmentioning
confidence: 99%
“…The elliptic inclusion problems in antiplane elasticity and plane elasticity are some particular problems in the field of inclusion problem [4][5][6][7][8][9]. For the antiplane problem of an elastic elliptical inclusion with uniform eigenstrains and arbitrary remote loading, a general solution was provided [4].…”
Section: Introductionmentioning
confidence: 99%